Ecosystem-based fisheries management requires broader performance indicators for the human dimension. (October 2019) - Hornborg, Sara; van Putten, Ingrid; Novaglio, Camilla; Fulton, Elizabeth A.; Blanchard, Julia L.; Plagányi, Éva; Bulman, Cathy; Sainsbury, Keith
Abstract: Ecosystem-based fisheries management (EBFM) is a globally mandated approach with the intention to jointly address ecological and human (social-cultural, economic and institutional) dimensions. Indicators to measure performance against objectives have been suggested, tested, and refined but with a strong bias towards ecological indicators. In this paper, current use and application of indicators related to the human dimension in EBFM research and ecosystem models are analysed. It is found that compared to ecological counterparts, few indicators related to the human dimension are commonly associated with EBFM, and they mainly report on economic objectives related to fisheries. Similarly, in the most common ecosystem models, economic indicators are the most frequently used related to the human dimension, both in terms of model outputs and inputs. The prospect is small that indicators mainly related to profitable fishing economy are able to report on meeting the broad range of EBFM objectives and to successfully evaluate progress in achieving EBFM goals. To fully conform with EBFM principles, it is necessary to recognise that ecological and human indicators are inter-dependent. Moreover, the end-to-end ecosystem models used in EBFM will need to be further developed to allow a fuller spectrum of social-cultural, institutional, and economic objectives to be reported against. Highlights: Ecosystem-based fisheries management (EBFM) includes ecological and human objectives. Research focus has been on mainly ecological EBFM indicators. Human indicators and to which EBFM objectives they relate were reviewed. Only a few indicators were commonly used, mainly related to fishing economy. It is important to appropriate address all dimensions in operationalizing EBFM.